Performance analysis of a multi-user multiple input multiple output (MIMO) wireless link over a ralyleigh and rician fading environment - Rahman, Md. Atikur; Islam, Syed Amirul; Atique, Nashad (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.